2020
DOI: 10.2147/phmt.s267892
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Severe Acute Malnutrition Among HIV-positive Children Receiving HAART in Public Health Institutions of North Wollo Zone, Northeastern Ethiopia: Unmatched Case–Control Study</p>

Abstract: Background Over half of the children living with HIV/AIDS suffer from severe acute malnutrition especially in countries having food insecurity like Ethiopia. However, determinants of severe acute malnutrition among HIV-positive children receiving care and treatment in antiretroviral therapy clinics in Ethiopia are not abundantly investigated. The aim of this study was to assess the determinants of severe acute malnutrition among HIV-positive children receiving highly active antiretroviral therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
3
11
2
Order By: Relevance
“…This study revealed that children in the advanced WHO clinical stages were more likely to be wasted. This is in line with previous studies conducted in Eastern Ethiopia children [ 5 , 22 ]. This can be explained by the fact that HIV-positive people who have advanced stage of the disease are more vulnerable to opportunistic infections, making them susceptible to undernutrition by decreasing intake, by altering digestion, absorption, and metabolism as well as by increasing energy need [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study revealed that children in the advanced WHO clinical stages were more likely to be wasted. This is in line with previous studies conducted in Eastern Ethiopia children [ 5 , 22 ]. This can be explained by the fact that HIV-positive people who have advanced stage of the disease are more vulnerable to opportunistic infections, making them susceptible to undernutrition by decreasing intake, by altering digestion, absorption, and metabolism as well as by increasing energy need [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, children who had recurrent oral lesions were more likely to be wasting. This is in line with previous studies conducted in Ethiopia-Gojam, Cameron, and North Wollo [ 8 , 14 , 22 ]. This is due to children with oral lesions have difficulty of swallowing, which reduces the amount of food intake that leads to nutritional imbalance less than body requirement.…”
Section: Discussionsupporting
confidence: 93%
“…In 2018, an estimated 1.7 million children (aged <15 years) were living with HIV worldwide [ 13 , 14 ]. In the same year, in Ethiopia, 44229 children were diagnosed with HIV and 2055 died related to AIDS [ 9 , 15 ]. Undernutrition in all its forms remains a global public health burden that accounts for 45% of all deaths for people living with HIV [ 2 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated whether lower CD4 cell count, age, wealth index, adherence, food insecurity, and social support were risk factors for malnourished HIV-positive children's mortality [ 1 , 2 , 15 , 26 – 28 ]. Ethiopia is one of the countries hardest hit by the HIV epidemic as well as malnutrition [ 1 ]; the prevalence of undernutrition among HIV/AIDS children ranges from 12.3 to 46.8% [ 19 , 29 ] and is blamed for 57% of deaths [ 6 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute malnutrition (SAM), is the most extreme and visible form of undernutrition characterized, in children aged <60 mo, by extreme wasting and weight-for-height zscore (WHZ) below -3 SDs of the median WHO growth standards (14). SAM is common in HIV-infected children (15)(16)(17). Given the additional challenges facing HIV-infected infants and older children, such as opportunistic infections, growth faltering, and nutritional deficiencies, it is essential to review new information on the optimal feeding regimens for HIV-infected children with SAM.…”
Section: Introductionmentioning
confidence: 99%